New Species and New Records of Caddisflies (Insecta: Trichoptera) from India - Kaur, Simarjit; Garima, Deepti; Pandher, Manpreet Singh (Zootaxa, 2020)
In the publication by Kaur et al. (2020), the depository for the holotype of Chimarra gangtokensis new species was given as “(NPC)”, but no corresponding explanation for this acronym was provided in that publication. Therefore, the name of the species is unavailable (International Code of Zoological Nomenclature 1999, Art. 16.4.2). We clarify here that the holotype is a male deposited in the National Pusa Collection, Division of Entomology, Indian Agricultural Research Institute, Pusa, New Delhi (NPC). The purpose of this note is to validate the name of the new species from the publication date of this erratum by a reference to the original description and diagnosis as an indication (International Code of Zoological Nomenclature 1999, Art. 13.1.2).